Juventude e memória: lembranças de tempos recentes - Carlos Henrique dos Santos Martins (Ciências Sociais Unisinos)
This paper is part of a research project on young people who attend Black Music dances in the city of Rio de Janeiro. We start from the assertion that the young person is endowed with memory that is built in social relations and in different family contexts. In addition to the study about the building process of young people's memory, we observed the meaning of their memories and the role they play in their personal choices, as well as in the definition of values and norms to guide their paths. Thus, through the words of some of the young people interviewed, we present some articulations of the memory and the role of experience in the construction of their identities.